KONSEP DIRI, LINGKUNGAN KELUARGA DAN KEDISIPLINAN SISWA BERPENGARUH TERHADAP HASIL BELAJAR MATERI AKUNTANSI SISWA KELAS XI JURUSAN IPS, SMA ANTARTIKA SIDOARJO - Andriani, Fransiska Rista (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
This study aims to analyze the influence of self-concept, family environment and discipline of the student learning outcomes of accounting material partially and simultaneously. The population in this study were students of class XI IPS, SMA Antartika Sidoarjo in the academic year of 2013/2014 as many as 180 people, while the number of samples used were 124 people. The data collection techniques were used questionnaires, interviews, and documentation. Analysis method used multiple linear regression techniques. The results showed that selfconcept has no effect on learning outcomes. Family environment and discipline have a significant effect on learning outcomes. Self-concept, family environment, and discipline simultaneously has a significant effect on learning outcomes